2017
DOI: 10.1080/00140139.2017.1330968
|View full text |Cite
|
Sign up to set email alerts
|

Breast volume is affected by body mass index but not age

Abstract: It is recommended that bra cups must be designed to support the wide range and increasing magnitude of breast volumes exhibited by women. Practitioner summary: This original research provides evidence for bra designers and manufacturers on the range of breast volumes of women and the significant effect of BMI on breast volume. Bra cups need to be designed to support the wide range and increasing magnitude of breast volumes exhibited by women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 43 publications
3
55
2
Order By: Relevance
“…In the absence of prospective work on the topic, we cannot be certain about the scale of the increases in breast size with age nor that these occur independently of increases in body size around the same time. 8,9,67 Our findings have confirmed that larger breast size alone is sufficient to increase the odds for upper back pain; however, by not examining UBP severity in this study, we cannot be sure how bothersome this could be for mature-aged women. Low back pain deters physical activity participation 68 and reduces an individual’s sense of mental and physical wellbeing.…”
Section: Discussionsupporting
confidence: 56%
“…In the absence of prospective work on the topic, we cannot be certain about the scale of the increases in breast size with age nor that these occur independently of increases in body size around the same time. 8,9,67 Our findings have confirmed that larger breast size alone is sufficient to increase the odds for upper back pain; however, by not examining UBP severity in this study, we cannot be sure how bothersome this could be for mature-aged women. Low back pain deters physical activity participation 68 and reduces an individual’s sense of mental and physical wellbeing.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, it is recommended that at institutes where central lumpectomy is more frequently performed, the significance of distance of tumor from the nipple should be cautiously re-examined. Patients with high BMI have increased risks of receiving BCS, possibly because BMI is significantly associated with breast volume; further, it is known that the breast volume is two-three times greater in overweight and obese women (with high BMI) than in women with normal BMI [16]. Contrary to our results, in the previously presented Seoul National University Hospital (SNUH) nomogram, Kim et al [4] reported that the breast volume was not a predictive factor for BCS.…”
Section: Discussioncontrasting
confidence: 99%
“…Two studies that recruited only young women as participants 13,14 found no relationship between breast size and thoracic pain, suggesting that increased thoracic kyphosis and thoracic pain are likely to be long-term rather than immediate consequences of having large breasts. It should be noted, however, that the cohort numbers in these two studies was relatively small and that the breasts of the participants were not very large when comparing their bra sizes to objectively calculated breast volumes 9 .…”
Section: Introductionmentioning
confidence: 92%
“…These factors can also limit the ability of women with large breasts to participate in physical activity and, in chronic cases, necessitate breast reduction surgery 2,[6][7][8] . In addition to the well-documented negative consequences associated with reduced physical activity, physical inactivity due to symptoms associated with a large breast size, high BMI or musculoskeletal pain can lead to weight gain, as well as further increases in breast size because increases in BMI have been associated with increases in breast volume 9 . Alarmingly, the prevalence of this unique women's health problem is likely to escalate because the average bra size has increased over the past two decades from a small bra cup size (34B) to a large bra cup size (34DD) 10 .…”
Section: Introductionmentioning
confidence: 99%